Absent Man: the Dilemma of Memory and Hope - Harutyunyan, Edvard (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
In his way of searching for a meaningful life, modern man has become an existential traveler and sometimes tries to find himself outside the ongoing present of ’’now and here’’, in the past or in the future. In the first case he clung onto the past (already done), in the second case onto the future (will do it later). In the article a person with such a worldview is characterized as an "absent person", who does not have an intention to act and lives either by bethinking or hoping.